PRIMING IMPROVES GERMINATION OF MONOGERM RED BEET (BETA VULGARIS L.) CLUSTERS - B. Jagosz (Journal of Animal and Plant Sciences, 2018)
Priming treatments have been widely used in a large number of species to improve germination characteristics. The objective of the study was to accomplish the quality of clusters of monogerm red beet breeding lines using osmopriming. The aim of the first experiment was to find an effective priming treatment, which improved the seed germination characteristics of two genotypes, AR79 and W411, primed for 6-120 h with -1.0 MPa KNO , MgSO , PEG 6000 and 3 4 PEG 8000. Total treatments were 56, laid out in completely randomized design. The purpose of the second experiment was to see how storage for 6 and 12 months at 4 and 15°C affects the clusters germination of AR79, primed for 48 h with -1.0 MPa KNO and PEG 6000. Total treatments were 8, laid out in completely randomized design. Priming improved 3 all tested germination traits of both genotypes, such as the mean germination time, coefficient of uniformity of germination (CUG), coefficient of velocity, germination capacity and percentage (GC) of abnormal seedlings. Both lines presented the most optimal effects of germination after 48 h of priming with KNO and PEG 6000. Cluster storage 3 contributed to the deterioration of their germination. The type of priming solution had no effect on cluster germination after storage. Better results were obtained with clusters stored for 6 than those for 12 months only for the CUG and GC. The storage of clusters at 4°C was more advantageous for germination features than storage at 15°C. hybrids. Thus, the current red beet breeding program is
Keywords: abnormal seedlings; COV; CUG; germination capacity; MGT; osmotic conditioning.